1997
DOI: 10.1128/jb.179.4.1317-1323.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of the P97 swine cilium adhesin gene of Mycoplasma hyopneumoniae

Abstract: Colonization of the swine respiratory tract by Mycoplasma hyopneumoniae is accomplished by specific binding to the cilia of the mucosal epithelial cells. Previous studies have implicated a 97-kDa outer membraneassociated protein, P97, that appeared to mediate this interaction. In order to further define the role of P97 in adherence to porcine cilia, the structural gene was cloned and sequenced, and the recombinant products were analyzed. Monoclonal antibodies were used to identify recombinant clones in a genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 31 publications
2
96
2
1
Order By: Relevance
“…TnlOOO insertional mutagenesis studies mapped the mAb F1B6 binding epitope to a region between amino acid residues 704 and 1004 in the carboxy terminus of P97 which encompassed the 5-aa repeat region (RR1) but not the 10-aa repeat region (RR2). The insertion of TnlOOO in RR2 did not affect ciliary binding or the ability of mAb F1B6 to bind to P97, suggesting that RR2 is not involved in adhesion (Hsu et al, 1997). DNA sequence analysis revealed the presence of an ORF for a 124 kDa protein; however amino-terminal sequence analysis of P97 (Zhang et al, 1995) mapped 195 aa internal to the start codon, suggesting that the 124 kDa antigen was a precursor in M. hyopneumoniae that is subsequently processed to 102 kDa by proteolytic cleavage (Hsu et al, 1997).…”
Section: One Of the Repetitive Regions Encoded Amino Acids A(t)-k-p-ementioning
confidence: 99%
See 2 more Smart Citations
“…TnlOOO insertional mutagenesis studies mapped the mAb F1B6 binding epitope to a region between amino acid residues 704 and 1004 in the carboxy terminus of P97 which encompassed the 5-aa repeat region (RR1) but not the 10-aa repeat region (RR2). The insertion of TnlOOO in RR2 did not affect ciliary binding or the ability of mAb F1B6 to bind to P97, suggesting that RR2 is not involved in adhesion (Hsu et al, 1997). DNA sequence analysis revealed the presence of an ORF for a 124 kDa protein; however amino-terminal sequence analysis of P97 (Zhang et al, 1995) mapped 195 aa internal to the start codon, suggesting that the 124 kDa antigen was a precursor in M. hyopneumoniae that is subsequently processed to 102 kDa by proteolytic cleavage (Hsu et al, 1997).…”
Section: One Of the Repetitive Regions Encoded Amino Acids A(t)-k-p-ementioning
confidence: 99%
“…Failure to detect sequence variation among three independent clones containing 5' adhesin gene sequences and the absence of more than a single strongly hybridizing fragment in Southern blot experiments (see Fig. 5b) suggested that only a single copy of the adhesin gene resides in M. hyopneumoniae strain J. Amino-terminal amino acid sequence data from purified P97 (Hsu et al, 1997) and Mhpl (King et al, 1997) revealed that the first 195 aa had been removed and suggested that the ciliary adhesin was produced from a 124.5 kDa precursor which was subsequently processed to 102 kDa by proteolytic cleavage. Western blots of whole-cell lysates of different strains of M. hyopneumoniae reacted with anti-94 kDa serum (Fig.…”
Section: A-f-s-y-k-l-e-y-t-d-e-n-k-l-s Immediatelymentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibodies F1B6 and F2G5, which recognize the R1 cilium binding region in P97 (Zhang et al ., 1995), are able to reduce adherence of M. hyopneumoniae to respiratory cilia by approximately 70%. Purified recombinant P97 inhibits adherence of M. hyopneumoniae cells to cilia in a dose-dependent manner (Zhang et al ., 1995) and binding of recombinant P97 to porcine respiratory cilia is inhibited by sulphated glycosaminoglycans (Hsu et al ., 1997). Consistent with these observations, P97 was recently shown to possess two heparin-binding domains (Jenkins et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…hyopneumoniae ao cílio suíno em um teste de inibição da aderência "in vitro" (ZHANG et al, 1995), sugerindo que a região R1 da adesina P97 possui papel fundamental na patogenia da PES, tornando-a uma forte candidata a antígeno vacinal. O gene que codifica a adesina P97 (p97) foi clonado e seqüenciado (HSU et al, 1997). A análise deste gene revelou uma open reading frame (ORF) que codifica para uma proteína de 125 kDa, a qual apresenta um domínio transmembrana hidrofóbico e um peptídeo sinal.…”
Section: F1b6 E F2g5 Estes Mabs Bloquearam a Aderência Deunclassified